The optimal hedge ratio and hedging effectiveness of Malaysia crude palm oil futures: a comparative analysis of static and dynamic models - Bea, Khean Thye (2020)
This study examines the hedging effectiveness of Malaysia crude palm oil futures (FCPO) with different time to maturity by employing the static hedging models of naïve, ordinary least square (OLS) and dynamic hedging models of Diagonal-Baba-Engle-Kraft-Kroner (Diag-BEKK GARCH), constant conditional correlation (CCC GARCH) and Dynamic conditional correlation (DCC GARCH). First, the study found that the far month FCPO is not an effective hedging tool for the CPO spot while the hedging performance for near month FCPOs is relatively close to each other regardless of the contract liquidity. Second, the unconditional correlation model of Diag-BEKK GARCH is unable to sustain its performance in out-of-sample and the performance of CCC GARCH model has achieved the highest risk reduction of 45.78% in out-of-sample. Although DCC-GARCH model is unable to achieve the highest variance reduction, but the overall hedging performance is relatively stable and consistent. When the model specification is getting complex, the superiority of DCC-GARCH model will be showed. Lastly, the ignorance of basis effect will result in a lower risk reduction but the directional asymmetric basis effect might not always improve the hedging effectiveness.